(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ventsova I, Safonov V. 2021. Biochemical criteria for the development mechanisms of various reproduction disorders in dairy cows. Biodiversitas 22: 4997-5002. The article presents the evaluation of peroxide, antioxidant, and hormonal conditions of high-producing red-and-white dairy cows in the physiological and pathological course of pregnancy and the postpartum period. The blood concentration of malonic dialdehyde, stable nitric oxide metabolites, S-nitrosothiols, vitamins E and C, carotin, gonadal, corticosteroid, and thyroid hormones, as well as activity of GPx, GR, SOD, catalase, and ceruloplasmin, were estimated to define major disorder-provoking factors. Analysis of the data shows that ketosis-gestosis syndrome during pregnancy, postpartum metritis, and gonadal dysfunction occur mainly because of oxidative stress in the context of unbalanced peroxide responses and antioxidant protection. Levels of malonic dialdehyde compared to healthy animals increased by 42.3%, 75%, 56.6%, respectively, as also enzyme activities of GR by 26%, 68.1%, 30.1% and catalase by 17.3%, 45.1%, and 23.9%, correspondingly. The endocrine status indicators in the animals with ketosis-gestosis syndrome changed as follows: progesterone levels were 29.5% lower in cows, 17?-estradiol and cortisol were 20.8% and 14.7% lower, respectively. In animals with inflammatory uterine diseases and depressing reproductive glands, progesterone level was 2 and 3 times lower than in healthy animals, the content of cortisol was 17.6% and 25.1% lower, and testosterone decreased by 21.4% and 75.1%, respectively.